Research progress on the pharmacological activity, biosynthetic pathways, and biosynthesis of crocins - Hua, Zhongwei; Liu, Nan; Yan, Xiaohui (Beilstein Journal of Organic Chemistry, 2024)
Crocins are water-soluble apocarotenoids isolated from the flowers of crocus and gardenia. They exhibit various pharmacological effects, including neuroprotection, anti-inflammatory properties, hepatorenal protection, and anticancer activity. They are often used as coloring and seasoning agents. Due to the limited content of crocins in plants and the high cost of chemical synthesis, the supply of crocins is insufficient to meet current demand. The biosynthetic pathways for crocins have been elucidated to date, which allows the heterologous production of these valuable compounds in microorganisms by fermentation. This review article provides a comprehensive overview of the chemistry, pharmacological activity, biosynthetic pathways, and heterologous production of crocins, aiming to lay the foundation for the large-scale production of these valuable natural products by using engineered microbial cell factories.
Keywords: biosynthetic pathway; crocetin; crocins; metabolic engineering; pharmacological activity